2013
DOI: 10.1007/s13594-013-0148-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment, final pH of acidification, and homogenization pressure on the texture properties of cream cheese

Abstract: International audienceCream cheese is a good model for studying the effect of process and formulation changes on the modification of product texture. In this study, the intensity of heat treatment (72 °C/20 s or 94 °C/40 s), the final pH of acidification (pH 5.2 or 4.9) and the homogenization pressure (0, 5, 20, or 60 MPa) were studied. Special attention was paid to the whey protein denaturation, casein micelle dissociation, fat globule size and their relations with structural, rheological, and sensory charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 18 publications
3
41
1
6
Order By: Relevance
“…Similar results have been reported at homogenisation pressures of 0, 5, 20 and 60 MPa in cream cheese by Coutouly et al . ().…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Similar results have been reported at homogenisation pressures of 0, 5, 20 and 60 MPa in cream cheese by Coutouly et al . ().…”
Section: Resultsmentioning
confidence: 97%
“…This differs from the observation of other researchers (Brighenti ; Coutouly et al . ) who observed an increase in fat droplet size with increase in homogenisation pressure.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Abd El-Gawad et al (2012) revealed that Mozzarella cheese made from homogenized buffalo milk was firmer and more elastic than non-homogenized samples. Coutouly et al (2014) reported that increasing the homogenization pressure led to a decrease in fat globule size and consequently an increase in the cream cheese firmness. Sohrabvandi et al (2013) observed that homogenization at 50 bar after heating led to the highest hardness, whilst non-homogenized and homogenized treatments at 150 bar before heating resulted in the lowest hardness.…”
Section: Introductionmentioning
confidence: 99%